Pengaruh Slow Stroke Back Massage terhadap Penurunan Depresi pada Pasien Pasca Stroke di RS. Harapan dan Doa Kota Bengkulu - Erni Buston; Sariman Pardosi; Winda Winda (Universitas Gorontalo, 2022)
Stroke disease becomes a health problem and the main cause of disability that affects individuals and families. The condition of stroke patients in general can be recovered but with residual symptoms lasting 3-6 months even up to many years. The main factors that can inhibit healing in stroke patients are depression arising in post-stroke. The purpose of this research is to influence effects of slow stroke back massage toward decreasing depression of post-stroke patients in Poly Nerve RS. Harapan Dan Doa Bengkulu City, 2020. The research used quasi experimental with pre-test and post-test one group design. Total samples of 25 respondents consists of 1 group. The sampling technique used purposive sampling. The instrument used beck depression inventory II with 21 questions. The analysis used t-test at α <5%. The results showed that the mean value of depression before giving slow stroke back massage is 28.24 and after slow stroke back massage the average value of depression value is 22.40. There is an influence on the value of depression before and after the slow stroke back massage (p value = 0.000). Slow stroke back massage can decreasing depression of post-stroke patients in Poly Nerve RS. Harapan Dan Doa Bengkulu City.